Advances in Robot Kinematics: Motion in Man and Machine 2010
DOI: 10.1007/978-90-481-9262-5_45
|View full text |Cite
|
Sign up to set email alerts
|

Singularity-Invariant Leg Rearrangements in Stewart–Gough Platforms

Abstract: A la meva família, pel seu recolzament incondicional. AgraïmentsM'agradaria expressar la meva sincera gratitud al professor Federico Thomas.La seva inestimable guia al llarg d'aquests 4 anys m'ha permès no només realitzar aquesta tesi, sinó aprendre queés la recerca i a estimar la professió a través del seu entusiasme en els projectes però també de la seva mirada crítica, sempre constructiva.També voldria agrair a la professora Carme Torras el temps que m'ha dedicat, al llarg de tots els treballs que hem fet j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 59 publications
(101 reference statements)
0
27
0
Order By: Relevance
“…As the solvability condition of this system is equivalent with the criterion given in Eq. (12) of [48], also the singularity surface of the manipulator does not change by adding legs of Λ. Moreover, it was shown in [47], that in the general case Λ is oneparametric and that the base anchor points as well as the corresponding platform anchor points of Λ are located on planar cubic curves C and c (see Fig.…”
Section: Recent Results On Sg Platforms With Self-motionsmentioning
confidence: 96%
See 1 more Smart Citation
“…As the solvability condition of this system is equivalent with the criterion given in Eq. (12) of [48], also the singularity surface of the manipulator does not change by adding legs of Λ. Moreover, it was shown in [47], that in the general case Λ is oneparametric and that the base anchor points as well as the corresponding platform anchor points of Λ are located on planar cubic curves C and c (see Fig.…”
Section: Recent Results On Sg Platforms With Self-motionsmentioning
confidence: 96%
“…The correspondence between the points of C and c in the complex projective extension 3 P of the Euclidean 3-space is determined by the geometry of the manipulator 6 1 ,..., M m and can be computed according to [47,48]. As this correspondence has not to be a bijection (see Fig.…”
Section: Assumption 1 We Assume That There Exist Such Cubics C and Cmentioning
confidence: 99%
“…The same implicit equation (5) was deduced [22] by imposing that the squared leg lengths before and after a leg rearrangement -for an arbitrary fixed pose of the moving platform-are affinely related. This kind of reconfigurations keeps not only the singularity locus unchanged, but also the resulting kinematic equations are essentially the same.…”
Section: Geometric Structure Of the Singularitiesmentioning
confidence: 99%
“…. , M 6 is not architecturally singular, then at least a one-parametric set of legs exists, which can be attached to the given manipulator without changing the forward kinematics [5,9] and the singularity set [2] of the manipulator. Moreover, it was shown that in general the base anchor points M i as well as the corresponding platform anchor points m i are located on planar cubic curves C and c, respectively.…”
Section: Types Of Self-motionsmentioning
confidence: 99%